The Barriers To Exclusive Breastfeeding: A Case-Control Study Among Mothers In Gorontalo City, Indonesia - Sarmin, Sukati; Makiyah, Sri Nabawiyati Nurul; Rokhanawati, Dewi (Politeknik Kesehatan Kemenkes Mamuju, 2023)
Exclusive breastfeeding is one of the important contributions to reducing maternal mortality, infant mortality, economic and environmental benefits. However, mothers still face many barriers during exclusive breastfeeding. This study aims to explain the perceived barriers to breastfeeding and find the most dominant barriers to breastfeeding. This type of research is quantitative research with analytic observational design and case-control method. The number of respondents in this study was 86 breastfeeding mothers, with a division of 43 mothers into case groups and 43 mothers into control groups. Sampling was determined by simple random sampling technique using an online number randomization application, namely random generator. Data were obtained from an original survey using an online questionnaire distributed through a social media platform in the form of a google form link. The results showed that barriers to exclusive breastfeeding from the social aspect, namely inadequate support from health care providers, were the most visible, followed by barriers from the maternal and infant aspects. Lack of health worker support (AOR= 22.621) was considered the main barrier to exclusive breastfeeding for six months among mothers in Gorontalo City, Indonesia. This was followed by lack of knowledge on breastfeeding. The lowest barrier was family support. Research on barriers to exclusive breastfeeding can help nurses and midwives develop breastfeeding promotion programs to increase exclusive breastfeeding among women in Gorontalo City, Indonesia.